Rna Buffering Fluorogenic Probe for Nucleolar Morphology Stable Imaging And Nucleolar Stress‐Generating Agents Screening - Wenchao Jiang; Qinglong Qiao; Jie Chen; Pengjun Bao; Yi Tao; Yinchan Zhang; Zhaochao Xu (Advanced Science, 2024)
Abstract In the realm of cell research, membraneless organelles have become a subject of increasing interest. However, their ever‐changing and amorphous morphological characteristics have long presented a formidable challenge when it comes to studying their structure and function. In this paper, a fluorescent probe Nu‐AN is reported, which exhibits the remarkable capability to selectively bind to and visualize the nucleolus morphology, the largest membraneless organelle within the nucleus. Nu‐AN demonstrates a significant enhancement in fluorescence upon its selective binding to nucleolar RNA, due to the inhibited twisted intramolecular charge–transfer (TICT) and reduced hydrogen bonding with water. What sets Nu‐AN apart is its neutral charge and weak interaction with nucleolus RNA, enabling it to label the nucleolus selectively and reversibly. This not only reduces interference but also permits the replacement of photobleached probes with fresh ones outside the nucleolus, thereby preserving imaging photostability. By closely monitoring morphology‐specific changes in the nucleolus with this buffering fluorogenic probe, screenings for agents are conducted that induce nucleolar stress within living cells.